PERAN CAMAT MENGOORDINASIKAN PENYELENGGARAAN KETENTERAMAN DAN KETERTIBAN UMUM DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2014 - Habibi, Novitra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is dilatatar with high number of security and public order disturbances and the number of theft cases that occurred in Kecamatan Tampan 2014. With this background, this research aims to know the Camat's efforts in coordinating the implementation of tranquility and public order in Tampan Direction in 2014 and to know the factors that affect the less optimal role of the Camat in coordinating the effort of organizing peace and public order in Kecamatan Tampan of 2014. The type and method of research used is qualitative research. Location and time of research is done in Kecamatan Tampan in 2014. Technique of collecting data of this research that is by doing interview and documentation equipped with supporting data obtained from mass media. The interview was conducted with Camat Tampan, kasi Trantib, kasi pembangunan masyarakat Kelurahan and Kanit Binmas Polsek Tampan. The results of this study explain that the role of sub-district is less than optimal in the implementation of peace and public order is evidenced by the number of disturbances of security and the highest order in Kecamatan Tampan. While the Camat effort to coordinate the implementation of peace and public order is to conduct coordination meeting of katibmas, coordinate with Sub-District Government, Police sector Tampan, Satpol PP, religious leaders and distribute circular letter to the community, while the factors causing less optimal role of Camat in effort penyenggraan ketentraman and public order is the absence of work plan that leads to activities of peace and public order, the inactivity siskamling existing in Kecamatan Tampan and lack of public participation. Keywords: Role, Camat, coordination, security and accessibility